Competitive dysfunction in pharmacies compounding: a Brazilian experience - Cukier, Rubens; da Silva, Orlando Roque; Venanzi, Délvio; Hasegawa, Haroldo Lhou (Brazilian Journal of Operations & Production Management, 2017)
This research aims to investigate the level of gaps in services offered by compounding pharmacies in Brazil. The research was conducted with a sample of 306 respondents comprised of owners, pharmacists and customers. We sought to assess the extent of gaps regarding competitive, strategic and operational dysfunctions, checking which are significant and the results of the service provided in relation to competitive factors valued by customers. The data collection instrument was a questionnaire validated model as SERVQUAL, published by Parasuraman et al. (1988). The statistical analysis used the software BioEstat v.05. The results demonstrate that there is a strong adhesion of the samples obtained and the quality dimension that stood out was reliability. In relation to the dysfunctions researched, the results pointed to a perfect interaction between agents which led us to accept that, as part of the pharmacies researched, there is no significant competitive dysfunction.